Presence of female professionals in the creative elite of advertising - Miguélez-Juan, Blanca (2024)
Gender equality is one of the Sustainable Development Goals (SDGs) of the 2030 Agenda. However, in the advertising industry, several studies have shown the low presence of women working in the field of creativity, occupying management positions and being part of festival juries. The aim of the study is to analyse the presence of women in the field of advertising festivals. The methodology is based on a quantitative analysis of the 2000 to 2023 editions of the Club de Creativos National Creativity Awards and the Cannes Lions International Festival of Creativity. The composition of the juries of both festivals, the special awards for professionals in the sector (cdec de Honor and Lion of St. Mark, respectively), the technical specifications of the grand prizes (National Grand Prize for Creativity and Grand Prix won by Spain, respectively) and the management teams of the organising entities are analysed in the indicated period. The results demonstrate the underrepresentation of women in advertising festivals, especially in the composition of the juries, in the special recognitions and in the technical sheets of the most outstanding campaigns, corroborating the findings of previous research. Despite the emerging initiatives that defend parity in the advertising profession, this equality is still not real, nor does it materialize in the events that make the industry visible and recognize its evolution: advertising festivals.